Interaction effects on galaxy pairs with Gemini/GMOS - II: oxygen abundance gradients - Rosa, D. A. (2014)
In this paper, we derive oxygen abundance gradients from HII regions located in 11 galaxies in eight systems of close pairs. Long-slit spectra in the range 4400?7300 Å were obtained with the Gemini Multi-Object Spectrograph at Gemini South (GMOS-S). Spatial profiles of oxygen abundance in the gaseous phase along galaxy discs were obtained using calibrations based on strong emission lines (N2 and O3N2).We found oxygen gradients to be significantly flatter for all the studied galaxies than those in typical isolated spiral galaxies. Four objects in our sample, AM 1219A, AM 1256B, AM 2030A and AM 2030B, show a clear break in the oxygen abundance at galactocentric radius R/R25 between 0.2 and 0.5. For AM 1219A and AM 1256B, we found negative slopes for the inner gradients, and for AM 2030B, we found a positive slope. All three cases show a flatter behaviour to the outskirts of the galaxies. For AM 2030A, we found a positive slope for the outer gradient, while the inner gradient is almost compatible with a flat behaviour. We found a decrease of star formation efficiency in the zone that corresponds to the oxygen abundance gradient break for AM 1219A and AM 2030B. For the former, a minimum in the estimated metallicities was found very close to the break zone, which could be associated with a corotation radius. However, AM 1256B and AM 2030A, present a star formation rate maximum but not an extreme oxygen abundance value. All four interacting systems that show oxygen gradient breaks have extreme SFR values located very close to break zones.The HII regions located in close pairs of galaxies follow the same relation between the ionization parameter and the oxygen abundance as those regions in isolated galaxies.